Identification of Novel Regulators of atonal Expression in the Developing Drosophila Retina - Melicharek, David (Genetics Society of America, 2008)
Atonal is a Drosophila proneural protein required for the proper formation of the R8 photoreceptor cell, the founding photoreceptor cell in the developing retina. Proper expression and refinement of the Atonal protein is essential for the proper formation of the Drosophila adult eye. In vertebrates, expression of transcription factors orthologous to Drosophila Atonal (MATH5/Atoh7, XATH5, and ATH5) and their progressive restriction are also involved in specifying the retinal ganglion cell, the founding neural cell type in the mammalian retina. Thus, identifying factors that are involved in regulating the expression of Atonal during development are important to fully understand how retinal neurogenesis is accomplished. We have performed a chemical mutagenesis screen for autosomal dominant enhancers of a loss-of-function atonal eye phenotype. We report here the identification of five genes required for proper Atonal expression, three of which are novel regulators of Atonal expression in the Drosophila retina. We characterize the role of the daughterless, kismet, and roughened eye genes on atonal transcriptional regulation in the developing retina and show that each gene regulates atonal transcription differently within the context of retinal development. Our results provide additional insights into the regulation of Atonal expression in the developing Drosophila retina.